Nano sized devices with shape memory - Chan, Shi Yi. (2011)
This paper aims to study the existence of the shape memory effect in nano-sized devices. The shape memory polymer (SMP) – polyurethane (PU) pellets are dissolved in dimethylformamide (DMF) solvent and dripped onto carbon nanotube (CNT) samples to fabricate PU nano-droplets on carbon nanotube through surface tension. Images and dimension of the droplets are taken and measured using the Scanning Electron Microscope (SEM). 5wt% PU-DMF solution was found to be effective in forming droplets of diameters ranging from a few micrometers to a few hundred nanometers. Various parameters which include the overall diameter, length and actual diameter (without the diameter of the CNT that it is bounded to) were analysed to understand the characteristics of the droplets formed. Indentation on the CNT samples were done using the micro-indenter and dimensions of the deformed (flattened) droplets found in the indented area were measured. DSC tests previously conducted had found the glass transition of the PU to be 55⁰C. By heating above its glass transition at 80⁰C, the dimensions of the PU droplets were re-measured and a range of percentage reduction from 5% to 35% in diameter was calculated upon comparison. It was demonstrated that the decrement in the diameter is due to the stimulation of shape recovery of the PU droplets upon heating.